Produtividade, estabilidade e adaptabilidade em progênies de eucalyptus urophylla s.t. blake - Pupin, Silvelise [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Prediction of genetic gains in breeding programs are not always compatible with those observed in practice and this is mainly due to the interaction of genotypes with environments (G´E). The aim of this study was to investigate the genetic variation, evaluate the significance of G´E and study the productivity , stability and adaptability simultaneously in five progeny trials of Eucalyptus urophylla, located at Anhembi-SP, Itatinga-SP, Itamarandiba-MG, Uberaba-MG and Selvíria-MS. The characters were: height, diameter at breast height, volume and survival. The genetic parameters and variance components were estimated by REML/BLUP procedure and methodologies HMRPGV (Harmonic Mean Relative Performance of Genetic Values) and AMMI (Additive Main effects and Multiplicative Interaction) were used to study the productivity, stability and adaptability. Individuals showed good growth. We detected genetic variation for characters and G´E interaction was significant. The methods allowed to identify productive, stable and adapted progenies. Parameters HMGV, RPGV and HMRPGV were efficient as standard for selection of genotypes of E. urophylla and the AMMI model allowed a very visual analysis of the behavior of genotypes in biplot’s graphics

A predição de ganhos genéticos em programas de melhoramento nem sempre é compatível com os observados na prática. Isso se deve principalmente à interação dos genótipos com os ambientes (G´A). O objetivo deste trabalho foi conhecer a variação genética, avaliar a significância da G´A e estudar simultaneamente a produtividade, estabilidade e adaptabilidade em cinco testes de progênies de Eucalyptus urophylla, localizados em Anhembi-SP, Itatinga-SP, Itamarandiba-MG, Uberaba-MG e Selvíria-MS. Os caracteres avaliados foram: altura de planta, diâmetro a altura do peito, volume de madeira e sobrevivência. Os parâmetros genéticos e componentes de variância foram obtidos pelo procedimento REML/BLUP e as metodologias MHPRVG (Média Harmônica da Performance Relativa dos Valores Genéticos) e AMMI (Additive Main effects and Multiplicative Interaction) foram utilizadas para estudo da produtividade, estabilidade e adaptabilidade. Os indivíduos apresentaram bom crescimento. Detectou-se variação genética para os caracteres e a interação G´A foi significativa. As metodologias permitiram identificar progênies produtivas, estáveis e adaptadas. Os parâmetros de MHVG, PRVG e MHPRVG foram eficientes como critérios para seleção de genótipos de E. urophylla e o modelo AMMI permitiu uma análise bastante visual do comportamento dos genótipos nos gráficos biplot’s
Keywords: Eucalipto; Genetica florestal; Melhoramento genetico; Eucalyptus